Assessment of the application of the FA280—a fully automated fecal analyzer for diagnosing clonorchiasis: a mixed-method study - Si-Yue Huang; Qing-Sheng Zeng; Xin-Fu Shi; Yun-Ting He; Yue-Yi Fang; Ying-Si Lai (Infectious Diseases of Poverty)
Abstract Background Clonorchiasis is an important foodborne parasitic disease in China caused by Clonorchis sinensis. Accurate and rapid diagnosis of this disease is vital for treatment and control. Traditional fecal examination methods, such as the Kato-Katz (KK) method, are labor-intensive, time-consuming, and have limited acceptance. The FA280, an advanced automated fecal analyzer, increases efficiency while significantly reducing labor load. This study aims to evaluate its performance, applicability, and scalability in clonorchiasis diagnosis to explore its potential application in the future. Methods A mixed-methods study integrating both quantitative and qualitative approaches was conducted. The quantitative component consisted of a cross-sectional survey in Xinhui District, Guangdong, China, to evaluate the diagnostic performance of the FA280. The positive rate and agreement between the FA280 and the KK method were evaluated using McNemar’s test. Additionally, Pearson’s Chi-square test was used to analyze the consistency of positive results between the two methods across various eggs per gram (EPG) groups under different cut-off values. The qualitative component included semi-structured individual interviews with medical staff and institutional administrators to examine the FA280’s applicability and potential for broader adoption, with thematic analysis of the data. Results In the quantitative study of 1000 participants, both the FA280 and KK methods detected clonorchiasis with a positive rate of 10.0%, achieving 96.8% agreement and showing no significant difference (P > 0.999). The kappa value was 0.82 (95% confidence interval: 0.76–0.88), indicating a strong agreement between the methods. The agreement rate for positive results between the two methods was significantly higher in the high infection intensity group compared to the low infection intensity group (P < 0.05). The qualitative study, which involved interviews with three medical staff and two administrators revealed that the FA280 outperformed the KK method in testing procedures, detection results, and user acceptance. The benefits, challenges, and suggestions of FA280 promotion were also emphasized. Conclusions This study demonstrated the FA280’s application value in clonorchiasis diagnosis by assessing its detection performance, applicability, and scalability. These findings contribute to the future prevention and control of the disease. Graphical Abstract